Exploring the distribution of energy consumption in a northeast Chinese city based on local climate zone scheme: Shenyang city as a case study. Issue 5 (September 2020) - Yang, Guang; Fu, Yanpeng; Yan, Minghui; Zhang, Jing
The local climate zone (LCZ) scheme is now used to investigate urban heat islands, which provides additional reference for energy consumption simulation. Based on the LCZ scheme, a LCZ mapping of Shenyang, a city in northeast China, was first constructed using the World Urban Database and Access Portal Tools (WUDAPT) Level 0 method. Subsequently, DeST-h was considered to simulate the energy consumption of urban buildings with concentration areas. The results show that with Shenyang being a severely cold area, the annual energy consumption of heating is approximately twice that of refrigeration for an individual building. The total energy consumption of open-distributed single buildings is higher than that of compact-distributed single buildings. Consequently, the unit cumulative energy consumption in compact-distributed buildings is higher than that in openly distributed building areas. The compact high-rise buildings (LCZ 1) have the highest energy consumption, with a unit annual energy consumption of 123, 771.150 MW·h, which is equivalent to 41, 257 tons of standard coal combustion power generation. Considering the energy consumption of residential buildings, the central high-rise buildings group and the compact centralized middle-rise buildings in the downtown area are high energy consumption areas. For future urban planning, design strategies such as energy-saving transformation and energy planning should be considered. The research results can provide a scientific basis and theoretical support for reducing building energy consumption, alleviating the urban heat island effect, and the development of modern urban planning.